Portable Wireless Traffic Light System (PWTLS) - Md Isa, Ida Syafiza; Mohd Shaari Azyze, Nur Latif Azyze; Ibrahim Tuani, Ahamed Fayeez (International Journal of Research in Engineering and Technology, 2014)
A Portable Wireless Traffic Light System using a microcontroller and wireless ZigBee is the best system to control the traffic flow during the road construction or maintenance. This traffic light is designed to solve the various type of hazard which may happen to the worker, flagman and also road users during the road construction. The communication between these two traffic lights is via wireless. Due to this it can be deployed anywhere because no wire is used. This system is equipped with the safety purpose where it is equipped with motion and infrared sensor to detect and count the number of vehicles to avoid any collision. This automated system can be used 24-hours in various weather conditions. This eliminate the limited working hours when using the flagman. This system is a low cost system where it uses microcontroller to control the system.